2012
DOI: 10.11606/issn.2316-9052.v30i1p1-4
|View full text |Cite
|
Sign up to set email alerts
|

Bromeliaceae na APA Santuário Ecológico da Pedra Branca, Caldas, Minas Gerais

Abstract: -(Bromeliaceae in the APA Santuário Ecológico da Pedra Branca, Caldas, Minas Gerais). The Environmental Protection Area Ecological Sanctuary of Pedra Branca is located in the municipality of Caldas, southern Minas Gerais state. In their 119 km 2 , the altitude is always above 1000m, reaching 1760m in the Pedra Branca. The region of Caldas raises interest since the mid-nineteenth century, when the naturalist Anders F. Regnell conducted extensive collections of local flora, listing several species of Bromeliacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
1
1
1
Order By: Relevance
“…Previous studies on the reproductive biology of A. distichantha carried out in areas located at lower latitudes reported hummingbirds and butterflies as its main flower visitors (Bernardello et al 1991;Araujo 1996;Buzato et al 2000;Scrok & Varassin 2011;Rosa & Monteiro 2012;Chupil 2013;Vizentin-Bugoni et al 2014). In contrast, in this study conducted at the southern distribution range of A. distichantha we found that carpenter bees are the main pollinators (in terms of visitation rates).…”
Section: Pollinator Assemblagecontrasting
confidence: 92%
See 1 more Smart Citation
“…Previous studies on the reproductive biology of A. distichantha carried out in areas located at lower latitudes reported hummingbirds and butterflies as its main flower visitors (Bernardello et al 1991;Araujo 1996;Buzato et al 2000;Scrok & Varassin 2011;Rosa & Monteiro 2012;Chupil 2013;Vizentin-Bugoni et al 2014). In contrast, in this study conducted at the southern distribution range of A. distichantha we found that carpenter bees are the main pollinators (in terms of visitation rates).…”
Section: Pollinator Assemblagecontrasting
confidence: 92%
“…The anthesis extends for only one day (Sazima & Sazima 1999;Scrok & Varassin 2011) and the nectar produced in the septal nectaries accumulates at the bottom of the flower (Bernardello et al 1991;Buzato et al 2000;Scrok & Varassin 2011;Oliveira et al 2016). Flowers are pollinated by hummingbirds, perching birds, bees, and butterflies (Araujo 1996;Sazima et al 1996;Sazima & Sazima 1999;Taura & Laroca 2001;Krömer et al 2006;Scrok & Varassin 2011;Bueno 2012;Rosa & Monteiro 2012;Chupil 2013;Vizentin-Bugoni et al 2014;Vossler et al 2014), and has been described as partially self-compatible (Scrok & Varassin 2011) or self-incompatible (Bianchi et al 2000), but a few (5%) fruit set was produced following self-pollination.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lithological formation of the Plateau, as well as the botanical specificities recorded, we can classify the Montana regions as Altitude Natural Fields (Kinoshita et al 2007;Pinheiro et al 2020). These regional Native Fields are still little known and most research carried out in these ecosystems has focused on botanical studies (Vasconcellos and Gouvea 1993;Matavelli and Monteiro 2012;Rezende et al 2013;Pinheiro et al 2020), which makes it necessary to investigate Vespidae in these ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, a Serra da Pedra Branca é uma área que merece atenção e, desde o século XIX, diversos naturalistas, com destaque para Anders Fredrik Regnell, vêm registrando coletas nesta localidade mostrando a rica flora vascular, formação geológica peculiar e que também se apresenta distinta do restante da Serra da Mantiqueira (Mota Machado & Menini Neto 2010, Rosa et al 2012, Rezende et al 2013. Nesta região predominam os campos de altitude, em um mosaico formado com as florestas estacionais e ombrófilas (incluindo fragmentos de floresta ombrófila mista).…”
Section: Introductionunclassified